Strength Preparedness of Young Sportsmen Predispositioned to Sprinter and Stayer Distances - Vladimir Davydov; Anna Mankevich; Olga Morozova (Lesya Ukrainka Volyn National University, 2018)
The article asserts the necessity to improve the sport training of swimmers, sprinters and stayers. The dynamics of strength preparedness indices of young swimmers belonging to experimental and control groups under the influence of training loads is studied. The influence of the main training aids on the indices of strength preparedness among young athletes aged 12-13 is defined. The divided strength preparedness of sprinters and stayers contributes to the realization of the capabilities of athletes in the competitive process.